ABDULLAH SAEED’S CONTEXTUAL APPROACH TO QUR’ANIC INTERPRETATION: EPISTEMOLOGY AND THE RECONSTRUCTION OF CONCEPTUAL MAPPING - Muhammad Barir (Tanzil: Jurnal Studi Al-Quran, 2026)
This study explores the epistemological foundations of Abdullah Saeed’s contextual hermeneutics within contemporary Qur’anic studies. In the twenty-first century, the growing demand to relate the Qur’an to changing social, ethical, and legal realities has made context-sensitive interpretation an important scholarly concern. Building upon and extending Fazlur Rahman’s double movement theory, Saeed introduces a contextual connector through a structured hierarchy of values that mediates between the historical meaning of the text and its contemporary application. This research employs a systematic conceptual mapping of Saeed’s interpretive framework, with primary reference to Interpreting the Qur’an: Towards a Contemporary Approach and Reading the Qur’an in the 21st Century. The findings indicate that Saeed offers several significant theoretical contributions, including refining interpretive stages, articulating ideal moral values, and classifying Qur’anic values hierarchically to guide contextual reasoning. This study reconstructs Saeed’s four-stage interpretive process into a simplified and integrative conceptual model that clarifies the epistemological relationship among text, interpreter, context, and application. Overall, Saeed’s framework reflects a coherent epistemological architecture that integrates sources of knowledge, methodological principles, and criteria of interpretive validity to support responsible and contextually grounded Qur’anic interpretation in contemporary Muslim societies. The coherence of the four stages of contextual interpretation constitutes a central element of Saeed’s epistemological validity; the omission of any stage would undermine the internal consistency of the method and consequently weaken its interpretive legitimacy. This study also identifies a reconstructed interpretive framework presented as a conceptual map.